Application of Snakehead Fish to Increase Liver Function of Rats after Experiencing Physiological Stress - Sunarno Sunarno; Siti Muflichatun Mardiati; Rully Rahadian (Biosaintifika: Journal of Biology & Biology Education, 2018)
Physiological stress due to nutritional deficiency accompanied by excessive activity can cause problems of energy deficiency required by the body. Energy shortage can affect the body weight, as well as the weight and histology of the liver. This study was conducted to examine and analyze the effect of snakehead fish meat supplementation in feed toward body weight, weight and hepatic histology in animals experiencing physiological stress. This study used 20 male Wistar rats consisting of 5 treatments with 4 replications. The treatment in this study consisted of control (P0) and treatment (P1: 5%, P2: 10%, P3: 15%, P4: 20%) groups. This research used Completely Randomized Design (RAL). The variables measured in this study were body weight, hepatic weight, central venous diameter and hepatocytes in the test animals. The data obtained were analyzed using Analysis of Variance (ANOVA) at 5% significance level and continued with Duncan test with 5% significance. The result of data analysis showed that fish snakehead fish supplementation in feed gave a significant effect to body weight, weight and histology of animal liver. Concentrations of snakehead fish supplements can increase the body weight, hepatic weight, and hepatic histology which was indicated by higher central venous and hepatocyte diameter values compared to other controls and treatments. The conclusion of this research is the provision of snakehead fish supplement (Channia striata) can increase the body weight, hepatic weight, central venous and hepatocytes diameter of Wistar rats with the most influential concentration of 20%. This evidence is useful in studying the mechanism of liver repair due to stress